IN THE EXPERIENCE OF THE INTERNATIONAL SYSTEM OF PROFESSIONAL EDUCATION EXISTING PROFESSIONAL COMPETITIONS (American Journal of Pedagogical and Educational Research, 2024)
This article is aimed at highlighting the experience of competitions held in the world's leading professional education systems, their types, organizational methods, and their impact on young professionals.